Effect of Competence, Work Environment, and Work Motivation on Employee Performance Through Job Satisfaction - Atika Fitry Kharisma; Rina Rosia (Sekolah Tinggi Ekonomi dan Perbankan Islam Mr. Sjafruddin Prawiranegara, 2022)
Employee performance of BPRS Bina Finansia Semarang is very important to study because this BPRS is one of the Islamic banks that is able to survive in the midst of market competition, especially competition between Sharia Banks in Semarang. This study analyzes competence, work environment, and work motivation through employee performance with job satisfaction as the intervening variable. The data collection method was carried out through questionnaires distributed to employees of Bank BPRS Bina Finansia Semarang. The sample used in this study was 32 respondents with a probability sampling technique. The data was processed with SmartPLS, analyzed with convergent validity, discriminant validity, composite reliability, Average Variance Extracted (AVE), Collinearity Statistics (VIF), path coefficient test, the goodness of fit test, bootstrap test, and Structural Equation Modeling (SEM) test. This study shows that competence has a negative and insignificant effect on employee performance. However, work environment, work motivation, has a negative and insignificant effect on job satisfaction. Other results show that job satisfaction can mediate the work environment on employee performance, but job satisfaction cannot mediate competence and work motivation on employee performance. This research is expected to be an additional reference for banks to improve quality in terms of employee performance. This research is extraordinary, for the sake of improvement in the future.